1996
DOI: 10.1007/bf01920710
|View full text |Cite
|
Sign up to set email alerts
|

Effects of progesterone and estradiol benzoate on superoxide dismutase activity in the brain of male rats

Abstract: The activities of mitochondrial, manganese-containing superoxide dismutase (MnSOD) and cytoplasmic, copper-zinc-containing superoxide dismutase (CuZnSOD) were measured in subcellular fractions of whole brain homogenates prepared from intact and gonadectomized (GDX) male rats, untreated or treated subcutaneously (sc) with a single dose of 2 mg progesterone (P) and/or 5 micrograms estradiol benzoate (EB). Neither MnSOD nor CuZnSOD was affected by the removal of the testes. Similarly, CuZnSOD activity was steady … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 15 publications
3
23
0
2
Order By: Relevance
“…We found no differences in levels of SOD1 protein expression between males and females for either brain region. Similarly, SOD1 activity in cytosolic fractions of whole brain homogenates was not affected by gonadectomy or sex hormone therapy (Pajović et al, 1993(Pajović et al, , 1996. Thus, it appears that sexassociated differences in ischemic cerebral susceptibility are not mediated by different basal expression levels of SOD1.…”
Section: Discussionmentioning
confidence: 92%
“…We found no differences in levels of SOD1 protein expression between males and females for either brain region. Similarly, SOD1 activity in cytosolic fractions of whole brain homogenates was not affected by gonadectomy or sex hormone therapy (Pajović et al, 1993(Pajović et al, , 1996. Thus, it appears that sexassociated differences in ischemic cerebral susceptibility are not mediated by different basal expression levels of SOD1.…”
Section: Discussionmentioning
confidence: 92%
“…Yet, we found no data concerning hormonal modulation of antioxidant enzyme activities during developmental processes. Our previous studies have shown that estradiol benzoate (EB) and progesterone modulate the activities of SOD, GPx, CAT, and glutathione reductase in brain of adult rats (16)(17)(18). The inhibition of brain mitochondrial manganese-SOD (MnSOD) activity by EB without affecting cytosol copper,zinc-SOD (CuZnSOD) activity was a response of rats of both sexes.…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant effect of estrogen has been regarded as the main mechanism for this hormone to protect skeletal and cardiac muscles (12), uterus (13), and liver (9) from damage. In brain, progesterone instead of estrogen exerts a significant antioxidant effect (14). Contrary to female steroids, testosterone has been shown to decrease the activities of SOD, CAT, and GSH-Px, leading to lipid peroxidation (15).…”
mentioning
confidence: 99%